1999
DOI: 10.1046/j.1523-1755.1999.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β regulates tubular epithelial-myofibroblast transdifferentiation in vitro

Abstract: TGF-beta1 is a key mediator that regulates, in a dose-dependent fashion, transdifferentiation of tubular epithelial cells into alpha-SMA+ myofibroblasts. This transdifferentiation is markedly enhanced by growth on collagen type I. These findings have identified a novel pathway that may contribute to renal fibrosis associated with overexpression of TGF-beta1 within the diseased kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
382
0
11

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(419 citation statements)
references
References 26 publications
26
382
0
11
Order By: Relevance
“…Furthermore, TGF-β modulates the expression of integrins, which are cell-surface receptors for ECM components, thereby facilitating cell adhesion and matrix deposition [39,40]. TGF-β also acts on (myo)fibroblasts, which are the main source of the increased ECM deposition in tissue fibrosis: TGF-β is a chemoattractant for fibroblasts [41], stimulates fibroblast proliferation [42], and regulates transdifferentiation of resident kidney cells into myofibroblasts [43].…”
Section: Transforming Growth Factor-betamentioning
confidence: 99%
“…Furthermore, TGF-β modulates the expression of integrins, which are cell-surface receptors for ECM components, thereby facilitating cell adhesion and matrix deposition [39,40]. TGF-β also acts on (myo)fibroblasts, which are the main source of the increased ECM deposition in tissue fibrosis: TGF-β is a chemoattractant for fibroblasts [41], stimulates fibroblast proliferation [42], and regulates transdifferentiation of resident kidney cells into myofibroblasts [43].…”
Section: Transforming Growth Factor-betamentioning
confidence: 99%
“…In vitro stimulation of tubule epithelial cells with TGF-␤1 induced a dose dependent, high rate of myofibroblast transformation that was abolished completely by the addition of a neutralizing anti-TGF-␤1 antibody. 59 Immediately after radiation, there was a significant and dose dependent increase in the levels of TGF-␤1 and collagen mRNA in rat tubule epithelial cells. 60 In addition, the expression of protease inhibitors, which block extracellular matrix (ECM) deposition (such as plasminogen activator-inhibitor 1), also increased.…”
Section: Radiation-induced Renal Fibrosismentioning
confidence: 94%
“…Submesothelial stromal cells, ovarian thecal cells, pericytes, hepatic perisinusoidal cells (hepatic stellate cells), pancreatic stellate cells or reactive macrophages have been also proposed as cells capable of expressing myofibroblastic phenotypes under pathological conditions [33][34][35][38][39][40] . Furthermore, it has been reported that renal epithelial cells may transdifferentiate into myofibroblastic cells in renal interstitial fibrosis [41][42][43][44] . It thus appears that so-called "myofibroblastic cells" in fibrotic lesions are generated from heterogeneous cell populations 45 .…”
Section: Myofibroblastsmentioning
confidence: 99%
“…2); these cytoskeletons represent useful markers of myofibroblastic differentiation 33,35 . It has been recently postulated that EMT, in which renal epithelial cells acquire myofibroblastic phenotypes, may contribute to the progressive renal fibrosis [41][42][43][44]60 . In the chronic model, it has been found that a number of cuboidal or flattened, single-or multi-layered epithelia in the fibrotic areas show a strong immunoexpression to α-SMA (Fig.…”
Section: Myofibroblasts In the Cisplatin-induced Rat Chronic Modelmentioning
confidence: 99%
See 1 more Smart Citation